Analysis of a continuous multicellular curved bridge deck using grillage analogy method - Ahmad, Suriati (2013)
The use of curved bridges in interchanges of modern highway systems has become increasingly popular for economic and aesthetic consideration. This research presents a comprehensive study on the analysis of a continuous multicellular bridge deck using Grillage Analogy Method. The elevated u-turn bridge at Taman Perling has been chosen as the case study. Two different cellular cross-section idealisation as an I-beam and a box-section are taken into consideration. Four different horizontal configuration of bridge deck namely straight, gentle curved, crooked and curved deck were considered in the study. The objectives are to determine the most optimum idealisation of the multicellular curved bridge deck transversely and longitudinally, to propose an approximate technique which is practical and economical and to validated the chosen approximation idealisation technique on the curved bridge deck with single column as middle support with other configuratios. All analyses were carried out using OASYS GSA software and the bridge deck is subjected to loadings in accordance with BS5400 and BD 37/01. The study concludes that the crooked curved configuration is the best representation of the curved bridge with the bending moments and shear forces having almost similar magnitude. There is no significant difference in analysis results when the deck is idealised as an I-beam or a box-section except for torsional moment distribution. Idealisation as crooked deck in longitudinal direction and I-beam in transverse direction was selected as the optimum idealisation of continuous multicellular curved bridge deck. However, the selected idealisation tecnique is not valid when the curved bridge deck with single column as middle support was modelled due to ambigious results obtained through the extended analysis